Sediment matters as a route of microplastic exposure: A call for more research on the benthic compartment - Sandgaard, Monica Hamann; Palmqvist, Annemette; Bour, Agathe; Grønlund, Sara Nicoline; Hooge, Asta; Selck, Henriette; Thit, Amalie; Syberg, Kristian (Frontiers in Marine Science, 2023)
Microplastics (MPs) are ubiquitous in the marine environment. Here, most MPs are expected to sink, either due to polymer density or environmental processes, such as biofouling, leading to sediment being proposed to act as a final sink for marine MPs. There is a discrepancy between the anticipated accumulation of MPs in the sediment compartment and the MP experiments conducted, since most MP effect studies have been conducted with pelagic species using water-only exposures. Here we address fundamental questions in relation to MP pollution to close the knowledge gap related hereto. A systematic literature search was performed to address these questions. We found that benthic invertebrates ingest MPs and that, even though these organisms evolutionary are adapted to handle particles, adverse effects may be observed upon ingestion of MPs. The analysis further revealed that there is a major knowledge gap on the impacts of sediment-associated MPs in marine, benthic invertebrates. To facilitate further and structured research within this topic, we recommend more studies with emphasis on the sediment as an important exposure pathway, and to focus on sediment-associated MP effects on benthic invertebrates. We recommend studies with ecological relevant exposure concentrations and ecological relevant exposure durations with emphasis on impacts on population- and community-level to reduce the knowledge gap within this central area of MP pollution research.